You can die ebook - Zanetti, Rebecca (Laurel Snow, 2023)
Luther meets Justified combined with Profiler in New York Times and USA Today bestselling author Rebecca Zanetti's exciting Laurel Snow Romantic Thriller series, set in the Pacific Northwest, featuring FBI Special Agent and rising star profiler Laurel Snow. For readers who love their thrillers centered around dysfunctional families, and their protagonists threatened by a serial killer. Men are dying in the Pacific Northwest, their bodies found near churches, charities, and counselling centers—each with valentine candy hearts shoved down their throats. They're good men with families and community ties—or so they seem until Laurel Snow and her team begin to investigate. Then the case takes a shockingly personal turn when the father she's never met, a former pastor, is attacked in exactly the same way. Now, besides solving the case, Laurel is on the hunt to discover where her father has been. Complicating things is Laurel's troubled half-sister, Abigail, a brilliant sociopath determined to prove that they've both inherited their father's malignant narcissism. Assisting Laurel is Washington Fish and Wildlife Captain Huck Rivers, a dangerous loner whose reliance on gut instinct puts him at odds with Laurel's coolly analytic approach. But the choice may be moot when the killer hones in on Huck's own dark secrets—putting him and Laurel squarely in the crosshairs. Praise for the debut Laurel Snow Thriller "Slow-burn romance and adrenaline-fueled thrills. . . . Both awkward Laurel and dogged Huck are refreshing departures from typical leads. . . . Readers will delight in this smart take on a classic trope." – Publishers Weekly (STARRED REVIEW) "A strong start to a new series promises more mystery and romance for an up-and-coming FBI profiler." — Kirkus Reviews STARRED REVIEW